Community Structure of Microalgae in Urban Small Lakes (Babakan, Kenanga, and Puspa) Under Anthropogenic Noise Variation: Implications for Biofuel Raw Material - Rubiantin Mesha Nauli Tambunan; Nining Betawati Prihantini; Santoso Soekirno; Nasruddin (Al-Kauniyah: Jurnal Biologi, 2026)
The global energy transition relies on renewable solutions such as microalgae. However, the diversity of microalgae in urban freshwaters, especially how anthropogenic noise affects them, remains unexplored. Our study explores three small lakes in Greater Jakarta—Babakan (South Jakarta), Puspa, and Kenanga (Universitas Indonesia, Depok, West Java)—that are becoming more exposed to anthropogenic noise, an evolving stressor with uncertain ecological effects on microalgae. Microalgae were identified from water samples collected from Babakan, Kenanga, and Puspa lakes, which had sound levels of -69.37 dB, -81.49 dB, and -99.43 dB, respectively. The results show that Kenanga Small Lake has the highest diversity (H' 2.44), while Puspa Small Lake has the highest dominance (D = 0.16) and evenness (E = 0.88). The "silent" Puspa Lake has the highest lipid percentage, which was 51.66%. While all environmental factors are interconnected to affect microalgal community structure and lipid percentage, these data point to a possible link between lower noise levels and better lipid yields, implying that indigenous microalgae from calmer urban contexts could be a feasible source of sustainable biofuel production.